2020
DOI: 10.3389/fonc.2020.593017
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Lipid Metabolism: The Critical Factors in Ovarian Cancer

Abstract: Ovarian cancer is one of the most malignant gynecological cancers around the world. In spite of multiple treatment options, the five-year survival rate is still very low. Several metabolism alterations are described as a hallmark in cancers, but alterations of lipid metabolism in ovarian cancer have been paid less attention. To explore new markers/targets for accurate diagnosis, prognosis, and therapeutic treatments based on metabolic enzyme inhibitors, here, we reviewed available literature and summarized sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 96 publications
4
59
0
Order By: Relevance
“…MAGL enzyme is overexpressed in a large variety of cells deriving from ovarian and colorectal cancers, and also has a key role in tumor progression [43,44]. Therefore, the new formulations of MAGL23 were tested on tumor cell lines inherent to ovarian [45] MAG23-AF and MAGL23 have comparable e cacy, in agreement with the results obtained from the nanocrystal characterization, which evidenced the maintenance of structural and chemical characteristics of the drug during the nanocrystallization procedure. Therefore, the drug delivery system allows to increase the water solubility without perturbing the molecule and consequently maintaining unaltered its activity on cells.…”
Section: Cell Viability Assaysupporting
confidence: 67%
“…MAGL enzyme is overexpressed in a large variety of cells deriving from ovarian and colorectal cancers, and also has a key role in tumor progression [43,44]. Therefore, the new formulations of MAGL23 were tested on tumor cell lines inherent to ovarian [45] MAG23-AF and MAGL23 have comparable e cacy, in agreement with the results obtained from the nanocrystal characterization, which evidenced the maintenance of structural and chemical characteristics of the drug during the nanocrystallization procedure. Therefore, the drug delivery system allows to increase the water solubility without perturbing the molecule and consequently maintaining unaltered its activity on cells.…”
Section: Cell Viability Assaysupporting
confidence: 67%
“…We also propose to target components of the NF-κB signaling pathway or lipid metabolism in combination with PARPi. As discussed above, both processes were highly activated following PARP1i and are recognized as emerging targets for pharmacological interventions for the treatment of cancer (38). Moreover, a first clinical phase I study with the small molecule inhibitor TVB-2640 targeting fatty acid synthase FASN demonstrated antitumor activity in combination with chemotherapy in ovarian cancer patients (42).…”
Section: Nomination Of Candidate Parpi Combination Therapy Targetsmentioning
confidence: 99%
“…In conclusion, we nominate four drugs to inhibit aforementioned targets in combination with PARPi in future preclinical investigations. These drugs have already shown their anti-tumor potential as single agent or in combination treatment in a variety of pre-clinical and clinical studies (38,41,43,44).…”
Section: Nomination Of Candidate Parpi Combination Therapy Targetsmentioning
confidence: 99%
“…Intra-abdominal tumors with a high frequency of omental metastases, such as ovarian cancer (OC), have become an important area of investigation revealing a role of adipocytes in promoting cancer lipid metabolism within the tumor microenvironment [2] . At the intracellular level, abnormal expression of key metabolic enzymes in fatty acid intake, synthesis, oxidation, and storage in OC cells has been associated with tumor-promoting properties [3] . Furthermore, for many of these enzymes, deregulation at the gene or/and protein level has been associated with prognostic implications in women with OC [3] .…”
mentioning
confidence: 99%
“…At the intracellular level, abnormal expression of key metabolic enzymes in fatty acid intake, synthesis, oxidation, and storage in OC cells has been associated with tumor-promoting properties [3] . Furthermore, for many of these enzymes, deregulation at the gene or/and protein level has been associated with prognostic implications in women with OC [3] . One such example is carnitine palmitoyltransferase (CPT), which catalyzes the decomposition of long-chain fatty acids and β-oxidation, and consists of two subtypes, CPT1 and CPT2 [3] .…”
mentioning
confidence: 99%